The Effect of The Proportion of Turmeric Tamarind and Carrageenan on The Characteristics of Tamarind Jelly Drink. - Anggita Dhea Novita; Rima Azara; Syarifa Ramadhani Nurbaya; Rahmah Utami Budiandari (jurnal makanan tropis dan teknologi agroindustri, 2022)
This study aims to determine the effect of the proportion of turmeric acid and caragenan on the characteristics of jelly drink turmeric acid. This research was conducted using a factorial randomized block design (RAK) with the first factor being the turmeric and tamarind concentration treatment consisting of 3 levels, namely P1(75%: 25%), P2(50%:50%) P3(25%:75%) and the concentration of carrageenan consists of 3 levels, namely K1 (0.6%), K2 0, (8%), K3 (1.0%). The purpose of this study was to determine the effect of the ratio of carrageenan and turmeric acid on the pH value, viscosity, total dissolved solids, vitamin C, water content, antioxidants, and organoleptic tests (color, aroma, taste and texture) of jelly drink sour turmeric. Parameters The best treatment was jelly drink turmeric acid with turmeric acid concentration 75%: 25% and carrageenan concentration 1.0% which showed 0.16% vitamin, TPT 13.30 °Brix, pH 3.60, syneresis 6.95%, color value lightness 42.19, redness value –5.80, yellowness 23.71, aroma organoleptic 3.70 (neutral-slightly like), color organoleptic 3.90 (neutral-slightly like), taste organoleptic 4.70 (neutral - somewhat like), organoleptic texture 3.70 (neutral rather like).